Associations between fitness levels and self-perceived health-related quality of life in community - dwelling for a group of older females - Ferenc Ihász; Nikolett Schulteisz; Kevin J. Finn; Krisztina Szabó; Judit Gangl; Dóra Nagy; Pongrác Ács; András Oláh (BMC, 2020)
Abstract Background For older adults perceived quality of life has been linked to the ability to accomplish everyday tasks, a functional capacity which is thought to be based upon physical fitness. Although there is a relationship between physical activity and quality of life in older adults, the fitness of older adults and its relationship to quality of life needs more investigation. Therefore, the purpose of this study was to examine the associations between self-reported health-related quality of life and physical fitness in community-dwelling older females. Methods A cross-sectional study between four different age groups in retirement villages from two different places of the southern and western region of Hungary, among 173 women between the ages of 58 and 94 years old. We measured physical fitness using the Fullerton Test protocol and self-perceived health quality of life using the Short-Form Health Survey. Results Group means were different in six-minute walk distance, handgrip strength, and arm curls. The youngest group of females had higher scores of fitness in these categories as compared to the oldest grouping of women. Quality of Life were also difference across age groupings although not linear across the four age categories. Moderate level positive relationship was evident between perceived physical function and certain categories of physical fitness. Conclusions Sociability and self-motivation has a leading role in quality of life in elder population. It is worth putting a lot more emphasis into continuous cultural, social and most importantly into physical activity programs for elderly.